Survey of PDA management in very low birth weight infants across Italy - Benjamim Ficial; Iuri Corsini; Stefano Fiocchi; Federico Schena; Irma Capolupo; Rosa Maria Cerbo; Manuela Condò; Daniela Doni; Simona La Placa; Salvatore Porzio; Katia Rossi; Sabrina Salvadori; et al. (BMC, 2020)
Abstract Background The optimal management of PDA in very low birth weight (VLBW) infants is still controversial. Aim of our study was to investigate the management of PDA in the Italian neonatal intensive care units (NICU). Methods We conducted an on-line survey study from June to September 2017. A 50-items questionnaire was developed by the Italian Neonatal Cardiology Study Group and was sent to Italian NICUs. Results The overall response rate was 72%. Diagnosis of PDA was done by neonatologists, cardiologists or both (62, 12 and 28% respectively). PDA significance was assessed by a comprehensive approach in all centers, although we found a heterogeneous combination of parameters and cut-offs used. None used prophylactic treatment. 19% of centers treated PDA in the first 24 h, 60% after the first 24 h, following screening echocardiography or clinical symptoms, 18% after the first 72 h and 2% after the first week. In the first course of treatment ibuprofen, indomethacin and paracetamol were used in 87, 6 and 7% of centers respectively. Median of surgical ligation was 3% (1-6%). Conclusions Significant variations exist in the management of PDA in Italy. Conservative strategy and targeted treatment to infants older than 24 h with echocardiographic signs of hemodynamic significance seemed to be the most adopted approach.